Cardiovascular and sympathetic response to exercise after long-term beta-adrenergic blockade. Issue 6079 (9th July 1977) - Raine, A E; Pickering, T G
Abstract : The response to dynamic exercise was investigated in 21 patients receiving long-term treatment with beta-adrenoceptor antagonists and 22 controls. An electrocardiogram (ECG) and blood pressure were recorded before and after treadmill exercise, and plasma dopamine-beta-hydroxylase (DBH) activity was measured as an index of changes in sympathetic activity. Heart rate and blood pressure were lower at rest and throughout exercise in treated patients, although the pressor effect of exercise was not reduced. The ECG P-R interval was lengthened, and in addition the Q-T interval was prolonged. After exercise, plasma DBH activity was significantly increased in controls but not in treated patients. We conclude that long-term administration of beta-adrenergic blockers increases myocardial repolarisation time and reduces sympathetic nervous activity. These actions may contribute to the antiarrhythmic and hypotensive effects of long-term beta-blockade.